Foodgrain price stabilization in developing countries: Issues and experiences in Asia - Islam, Nurul; Thomas, Saji (International Food Policy Research Institute, 1996)
Should countries allow foodgrain prices to fluctuate freely or should they intervene to stabilize domestic prices? Traditional welfare analysis at the micro level concludes that economic benefits of price stabilization for consumers or producers, in general, tend to be small unless great importance is placed on risk aversion. In the simulation exercise undertaken in this study of micro level benefits to producers, which incorporate currently available estimates of risk aversion within an analytical framework based on the maximization of expected utility, price stabilization policies do not seem to yield large benefits. Analysts have questioned the appropriateness of the use of this framework and the treatment of risk aversion within the framework in view of the high priority that farmers in developing countries attach to economic security to avoid disaster and achieve a subsistence level of income. The macroeconomic benefits of price stabilization, including explored. Nevertheless, which the debate among analysts goes on, policymakers in many developing countries continue to pursue the objective of goodgrain price stabilization using different instruments with varying degrees of success and costs.